Spontaneous Crystallization of Perovskite Nanocrystals in Nonpolar Organic Solvents: A Versatile Approach for their Shape‐Controlled Synthesis. Issue 46 (26th September 2019) - Huang, He; Li, Yanxiu; Tong, Yu; Yao, En‐Ping; Feil, Maximilian W.; Richter, Alexander F.; Döblinger, Markus; Rogach, Andrey L.; Feldmann, Jochen; Polavarapu, Lakshminarayana
Abstract: The growing demand for perovskite nanocrystals (NCs) for various applications has stimulated the development of facile synthetic methods. Perovskite NCs have often been synthesized by either ligand‐assisted reprecipitation (LARP) at room temperature or by hot‐injection at high temperatures and inert atmosphere. However, the use of polar solvents in LARP affects their stability. Herein, we report on the spontaneous crystallization of perovskite NCs in nonpolar organic media at ambient conditions by simple mixing of precursor–ligand complexes without application of any external stimuli. The shape of the NCs can be controlled from nanocubes to nanoplatelets by varying the ratio of monovalent (e.g. formamidinium + (FA + ) and Cs + ) to divalent (Pb 2+ ) cation–ligand complexes. The precursor–ligand complexes are stable for months, and thus perovskite NCs can be readily prepared prior to use. Moreover, we show that this versatile synthetic process is scalable and generally applicable for perovskite NCs of different compositions. Abstract : Faster than fast : Shape‐controlled lead halide perovskite nanocrystals crystallize spontaneously at ambient conditions when precursor–ligand complexes are mixed directly in a nonpolar organic medium. Nanocubes and nanoplatelets have been obtained. This versatile synthetic process is generally applicable for a wide range of halide perovskite nanocrystals.